Interrogating the Neoliberal Lifecycle The Limits of Success - Clack, Beverley; Paule, Michele (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
In this timely collection, contributors from a number of disciplines discuss neoliberal visions of success, and the subsequent effects they have on the construction of the lifecycle. Frequently mentioned in popular political discourse, the notion of neoliberalism is often deployed as shorthand for the consensus that austerity is necessary and the hard-working individual can survive it. This volume unpicks and interrogates the term by engaging with the interface between the political ubiquity of neoliberal forms and its lived experience in neoliberal societies, cutting across a multiplicity of factors including gender, age, and access to education. Impressive in its wide scope and analysis, Interrogating the Neoliberal Lifecycle presents an informed discussion not only of the limits of the neoliberal paradigm but also of possible alternatives. .